Perceiving the Limits, Or: What a Pandemic Has Shown Us about the Climate Crisis - Ruitenberg, Claudia; Rathje, Elisa (Philosophical Inquiry in Education, 2022)
Education and, in particular, education concerned with our response to the climate crisis, can draw important lessons from the changed desires and re-evaluation of individual and collective values and goals that occurred as a result of the COVID-19 pandemic. The pandemic has shown us the importance of making the limits of the world perceptible. While the limits imposed by the pandemic and climate change alike can lead to serious losses, they also bring the possibility of discovering and enjoying new ways of living within those limits. We call attention in particular to forms of relinquishment that bring new pleasures.